Chromosomic numbers for three species of Cosmos section Discopoda (Asteraceae, Coreopsideae), with cytogeographic notes - Castro-Castro, Arturo; Vargas-Amado, Georgina; Castañeda-Nava, José Juvencio; Harker, Mollie; Munguía-Lino, Guadalupe; Santacruz-Ruvalcaba, Fernando; Rodríguez, Aarón (Instituto de Ecología, A.C., 2017)
Background and Aims: Cosmos section Discopoda (Asteraceae, Coreopsideae) is a model for studying polyploidy and aneuploidy. This section is monophyletic, including 24 herbaceous perennials with some polyploid species and others aneuploids. However, the chromosome numbers of some species are still unknown and their cytogeography has not been studied. Here the chromosome counts for three species are revealed and the ancestral levels of ploidy as well as geographical distributions of the different ploidy levels are compared.Methods: Previously known chromosome counts were retrieved and chromosome counts were made from vegetative parts of three species. After designating a ploidy level to each of 810 registers, including all species and through the use of a geographic information system, their distributions were analyzed based on those ploidy levels. In addition, using a maximum likelihood model, a reconstruction of ancestral ploidy was made.Key results: Cosmos nitidus and C. ramirezianus are diploids (2n=2x=24) while C. pseudoperfoliatus is tetraploid (2n=4x=48). To date, chromosome counts for the 20 species of Cosmos section Discopoda are known, of which 12 are diploids (2n=2x), six are exclusively polyploids (2n=4x, 6x, 8x), four are diploids and polyploids and there are two independent events of aneuploidy. The reconstruction of ancestral ploidy levels revealed that x=12 is the basic number of chromosomes in this section of Cosmos.Conclusions: A correlation between the ploidy levels and geographical ranges of the species of Cosmos section Discopoda does not seem apparent. In contrast, there does seem to be an increase in ploidy levels from south to north, with a concentration of polyploids in the northern area of the Sierra Madre Occidental.